Młodzieżowe rady miast i gmin – model działania i znaczenie dla rozwoju aktywności obywatelskiej młodego pokolenia - Kanclerz, Bożena; Konarczak, Agnieszka (Studia Edukacyjne, 2018)
The objective of the article is to present of issues on youth councils of cities and municipalities. The article describes the principles of creating youth councils for cities and municipalities. An important topic is also the description of building a civic socjety. The activity of youth in the local and school environment was also presented in the article.